The Effect of Empowerment Training in Protecting Adolescents from Substance Abuse on Self-Efficacy, Self-Esteem, and Assertiveness Levels - Koçak Uyaroğlu, Arzu; Özcan, Ayşe (Addicta: The Turkish Journal on Addictions, 2022)
The study aims to evaluate the effect of empowerment training in protecting adolescents from substance abuse on self-efficacy, self-esteem, and assertiveness levels. This a quasi-experimental research study with pretest-posttest design and a control group. The research sample was composed of 65 adolescents; 33 in the experimental group and 32 in the control group. The empowerment training program including 10 sessions in total, each lasting 45 minutes, was administered to the adolescents in the experimental group. Data were collected via the Adolescent Information Form, the Self-Efficacy for Protecting Adolescences from Substance Abuse Scale, the Rosenberg Self-Esteem Scale, and the Rathus Assertiveness Scale. In data analysis, variance analysis was used in repeated measures, and t test was used in independent groups. The increase in the self-efficacy mean scores of the adolescents in the experimental group in post-test and follow-up measurements was found to be statistically significant (p < .01). The difference between the experimental and control groups in terms of self-efficacy, self-esteem, and assertiveness scores was found to be statistically significant (p < .01). It was determined that the empowerment training program increased the self-efficacy levels of the adolescents in terms of protection from substance abuse, supported the development of selfesteem, and had a positive effect on their assertiveness.
Keywords: Adolescent; assertiveness; empowerment training; self-efficacy in protecting from substance abuse; self-esteem